PENGARUH KEPEMIMPINAN DAN BEBAN KERJA TERHADAP KINERJA KARYAWAN PT BANK MANDIRI (PERSERO) TBK.KCP CABANG JAKARTA CIBUBUR - Sri Lestari; Intan Agung Lestari (Sekolah Tinggi Manajemen IMMI Jakarta, 2023)
This study aims to determine the effect of leadership and workload on employee performance. The sample used in this study were employees of PT. Bank Mandiri (Persero) Tbk. KCP Jakarta Cibubur with a total of 45 people using Nonprobability Sampling, namely type (saturation sampling). The analysis in this study used validity test, reliability test, descriptive statistical test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression test, coefficient of determination test, F test and t test. Based on the results of the t test of tcount 9.299 ttable 1.681 with a significance value of 0.000 0.05. So, Ha is accepted, meaning that leadership has a partial effect on employee performance. Whereas for workload tcount 2.925 ttable 1.681, with a significance value of 0.006 0.05. So, Ha is accepted, meaning that workload partially affects employee performance. Based on testing the coefficient of determination (R2) of 0.925, it means that leadership and workload are able to explain (92.5%), the rest is influenced by other variables. The results showed that leadership and workload had a positive and significant effect on the performance of employees at PT. Bank Mandiri (Persero) Tbk. KCP Jakarta Cibubur.